2021
DOI: 10.3390/molecules26134095
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Efficacy of Ginseng against Respiratory Tract Infections

Abstract: Respiratory tract infections are underestimated, as they are mild and generally not incapacitating. In clinical medicine, however, these infections are considered a prevalent problem. By 2030, the third most comprehensive reason for death worldwide will be chronic obstructive pulmonary disease (COPD), according to the World Health Organization. The current arsenal of anti-inflammatory drugs shows little or no benefits against COPD. For thousands of years, herbal drugs have been used to cure numerous illnesses;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 172 publications
0
18
0
Order By: Relevance
“…Herbal therapy has been used to treat various ailments since ancient times, including chronic inflammatory diseases. Medicinal plants contain anti-inflammatory properties and have limited or no adverse effects [ 3 ]. T. aphylla is generally safe and harmless to humans.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal therapy has been used to treat various ailments since ancient times, including chronic inflammatory diseases. Medicinal plants contain anti-inflammatory properties and have limited or no adverse effects [ 3 ]. T. aphylla is generally safe and harmless to humans.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Currently, available medicines are distinctions or reproductions of constituents, combinations, and dilutions that exist in nature [ 2 ]. People’s interest in herbal medicines is currently increasing due to fewer or no side-effects [ 3 ]. Despite the minimal risk of adverse effects, the possibility of a medication interaction cannot be rejected.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 is an anti-inflammatory cytokine in the human immune response [ 80 , 81 ]. IL-10 was initially identified as a T-helper type 2 (Th2) cell product that suppressed cytokine generation in Th1 cells [ 82 , 83 ]. Additionally, probiotics may inhibit the production of pro-inflammatory cytokines by interfering with the mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) pathways [ 84 , 85 ].…”
Section: Probiotics Effect On Viral Replicationmentioning
confidence: 99%
“…than Gramnegative bacteria and concluded that environmental conditions affect the chemical and biological properties for G. glabra roots extracts. On the other hand, at last decades many studies described G. glabra as a potential medicinal compound for many purposes such as cure pulmonary inflammation treatment, Anticancer, antioxidant, liver disease treatment [32,33].…”
Section: -1 Chemical Analysis Of G Glabramentioning
confidence: 99%